Perbandingan Efektivitas Terapi Akupuntur dengan NSAID Terhadap Nyeri Low Back Pain (LBP) Pasien Rawat Inap di Rumah Rakit RSD KRMT Wongsonegoro Semarang - Purnami, Islina Dewi; Kamal, Siti Habibah (Sultan Agung Islamic University of Semarang, 2025)
ABSTRACT Background: Low Back Pain (LBP) is among the most prevalent musculoskeletal disorders, often resulting in functional limitations and reduced quality of life. The condition may originate from spinal structures, muscles, nerves, or adjacent tissues. Acupuncture, a traditional therapy involving the insertion of fine needles at specific points, represents one non-pharmacological treatment option. For LBP, the commonly targeted points include Shensu (BL 23), Dachangshu (BL 25), and Weizhong (BL 40) bilaterally to alleviate pain. The objective of this study is to compare the therapeutic effectiveness of acupuncture with nonsteroidal anti-inflammatory drugs (NSAIDs) in alleviating pain and improving functional outcomes in patients with LBP. Methods: This retrospective study compared the effectiveness of acupuncture and pharmacological therapy with NSAIDs in LBP patients at Wongsonegoro Hospital, Semarang. Medical records of 70 purposively selected patients were reviewed based on age, nonspecific LBP diagnosis, willingness to undergo therapy, and provision of informed consent. Acupuncture was administered four times at one-week intervals over a two-month period. Results: Acupuncture at BL 23, BL 25, and BL 40 demonstrated significant pain reduction. Wilcoxon test analysis yielded a significance level of 0.000 in both groups. In the NSAID group, 35 respondents experienced clinically meaningful improvement, whereas the acupuncture group showed a mean rank of 18.00, underscoring its effectiveness. Conclusion: Both NSAIDs and acupuncture were effective in reducing pain among LBP patients. Thibbun Nabawi acupuncture may be considered as a first-line or adjunctive therapy, particularly in patients with contraindications to NSAIDs or those opting for non-pharmacological interventions. Keywords: acupuncture; NSAID; LBP